Engaged Detachment: Camp and Homosexual Subjectivity - Mira, Alberto (Estudios LGBTIQ+, Comunicación y Cultura, 2021)
The definition of the term “camp” presents various difficulties for geographical and theoretical reasons. Although it is an ubiquitous practice in Anglo homosexual cultures, it is notoriously hard to pin down from an intellectual perspective. Susan Sontag’s 1964’s essay, which defined camp in terms of a "sensibility" but silenced the circumstances in which that sensibility is produced, was answered, in the 1990s, by other contributions that insisted on the specifically homosexual character of camp. This article builds on these responses to articulate a concept of camp based on its specificity within pre-Stonewall homosexual cultures, understanding camp as a discourse stemming from homosexual subjectivities in the era of repression. Subjectivity is both individual and social: it is the discursive position one occupies that always occurs in a pre-existing cultural lattice. The article links the key traits of homosexual camp (theatricality, irony, incongruity, humour) to that position by reading three distinctly camp traditions (diva-centered movies, Broadway musicals, and Athletic Model Guild gay porn) in terms of how they are linked to homosexual subject positions. I propose that, if camp discourse is "political," as some 1990s authors claimed, it also challenges the idea of "politics" as a progressive struggle. Finally, the article asks whether, given similar configurations of the homosexual experience, camp occurs in other cultures, using the parallels that the concept finds in Spain; although there is inevitably a camp discourse in Spanish culture, it is articulated by different means and requires a well-theorized attention to oral manifestations of pre-liberation Spanish homosexual culture.